Der Ausschluss aus der staatlichen Parteienfinanzierung Legalität, Legitimität und Folgen - Nikkho, Ramin (Studien zu Staat, Recht und Verwaltung, 2021)
A state should not be forced to fund those parties which try to combat its highest values. This thought was realized by a constitutional amendment to exclude parties from the state party financing. A defensive democracy is in narrow limits allowed to discriminate against certain political parties which try to overthrow its fundamental values to implement their own unconstitutional agenda. But the major intervention in the political competition though raises questions about its constitutional admissibility. The democracy itself basically precludes state interventions in the political competition to the detriment of a certain contestant. Those questions and the consequences for a thereby affected party are the main subject of this thesis.